Spelling on the Fly: Investigating a Pentop Computer to Improve the Spelling Skills of Three Elementary Students with Disabilities. - Doughty, Teresa Taber; Bouck, Emily C.; Bassette, Laura; Szwed, Kathryn; Flanagan, Sara (Assistive Technology)
The purpose of this study was to examine the effects of a pentop computer and accompanying spelling software on the spelling accuracy and academic engagement behavior in three elementary students with disabilities who were served in a resource room setting. Using a multiple baseline across students single subject research design, researchers determined student use of the pentop computer—the FLYPen™—and its spelling software may serve as an equivalent intervention to traditional spelling instruction. While academic engagement performance increased considerably for students when using the FLYPen™, results indicated little to no improvement over traditional instruction in spelling accuracy. Implications and suggestions for future research are presented.